N-Acetylcysteine in the Management of Acute Liver Failure From Sickle Cell Hepatic Crisis. Issue 8 (21st August 2019) - Zhang, Xiaojie; Burroughs, Sarah; Farooq, Ahmad; Bashir, Mustafa R.; Muir, Andrew J.; Patel, Yuval A.
ABSTRACT: N-acetylcysteine (NAC) has been well studied in the treatment of acetaminophen-induced and select non-acetaminophen-induced liver failure. However, its role in the management of sickle cell hepatic crisis resulting in acute liver failure (ALF) is unknown. We describe and discuss the novel and beneficial use of NAC in a 25-year-old man with ALF due to sickle cell hepatic crisis. We further review ALF in sickle cell disease and NAC in the treatment of non-acetaminophen-induced liver failure. Our case highlights the promising role of NAC in sickle cell-related liver injury.